Molecular systematics of the North American chub genus Macrhybopsis (Teleostei: Cyprinidae) - Echelle, Anthony A.; Lang, Nicholas J.; Borden, W. Calvin; Schwemm, Michael R.; Hoagstrom, Christopher W.; Eisenhour, David J.; Mayden, Richard L.; Bussche, Ronald A. Van Den (Zootaxa, 2018)
The North American fish genus Macrhybopsis (Teleostei: Cyprinidae) as presently conceived comprises 12 species and occurs in much of interior eastern North America. Variation in the mitochondrial ND2 gene and the nuclear S7 intron 1 reveal conflicting gene-tree relationships for deeper nodes, which are assumed to represent past introgression and heterospecific mitochondrial fixation. The results support monophyly for the wide-ranging M. aestivalis complex with successive sister relationships to M. gelida, M. meeki, and M. storeriana. The current species-level taxonomy of Macrhybopsis is generally supported. Species status is supported for the morphologically distinct M. australis and M. tetranema, both of which are genetically introgressed by M. hyostoma. The results agree with previous suggestions that the wide-ranging M. hyostoma harbors cryptic species. Similar crypticity is indicated for the poorly sampled M. storeriana; a sample from the Pearl River shows 8% ND2 divergence from two Mississippi River populations. Within the M. aestivalis complex, there are only two examples of geographic overlap among mtDNA phylogroups. One involves co-occurrence of the highly divergent M. marconis and M. cf. hyostoma, and the other is the detection of the apparently anthropogenic occurrence of mitochondrial DNA from a Red River form, either M. cf. hyostoma or M. australis, in the Cimarron River of the Arkansas River basin.